Gold Nanoparticle-Enhanced and Roll-to-Roll Nanoimprinted LSPR Platform for Detecting Interleukin-10 - Baek, Seung Hee; Song, Hyun Woo; Lee, Sunwoong; Kim, Jung-Eun; Kim, Yeo Hyang; Wi, Jung-Sub; Ok, Jong G.; Park, Jun Seok; Hong, Seonki; Kwak, Moon Kyu; Lee, Hye Jin; Nam, Sung-Wook (Frontiers in Chemistry, 2020)
Localized surface plasmon resonance (LSPR) is a powerful platform for detecting biomolecules including protein, nucleotide, and vesicle. Here, we report a colloidal Au nanoparticle-based assay to enhance the LSPR signal of a nanoimprinted Au strip structure. The induced colloidal Au nanoparticle leads a red-shift of the LSPR extinction peak, enabling us to detect IL-10 cytokines on the Au strip platform. For LSPR sensor fabrication, we employed a roll-to-roll nanoimprint process to create nanograting structures on polyethylene (PET) film. By angled deposition of Au upon the PET film, we demonstrated double-bent Au structure which has a strong LSPR extinction peak at ~760 nm. Upon the Au LSPR sensor, we performed an enzyme-linked immunosorbent assay (ELISA) protocol by forming a sandwich structure such as IL-10 capture antibody/IL-10/IL-10 detection antibody. To enhance the LSPR signal, we introduced a colloidal Au nanocube (AuNC) which is cross-linked to the IL-10 detection antibody of immunogold assay. We detected IL-10 cytokine as a model protein at nanomolar range by demonstrating up to 450 % signal enhancement of the extinction peak shift. We expect that the AuNC-assisted LSPR sensor platform can be utilized as one of the diagnostic tools by offering convenient and fast detection of LSPR signal.